2016
DOI: 10.4103/0975-962x.179375
|View full text |Cite
|
Sign up to set email alerts
|

A unique functional craniofacial suture that may normally never ossify: A cone-beam computed tomography-based report of two cases

Abstract: The premise of complete ossification of midpalatal suture in early adulthood still has its popularity, though conflicting data are emerging in the literature. A 49-year-old male and a 54-year-old female Iranian patient, both dentulous, were referred to a Maxillofacial Radiology Center to be evaluated for implant insertion. In cone-beam computed tomography (CBCT) evaluation, an in-ossified suture was found in anterior two-third of midpalatal region of both individuals. The application of clinical vignettes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The results of the present study in relation to the degree of ossification of the suture in the 10-year age groups showed that ossification increased with aging; however, some cases of completely open sutures were observed in the >20-year age groups. The results of the present study are consistent with those of previous studies ( 10 , 11 , 18 , 25 ). Nguyen (2008) carried out a study on 20 patients over 70 years of age and reported that the midpalatal suture is the only suture that might not close completely even in the elderly ( 11 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results of the present study in relation to the degree of ossification of the suture in the 10-year age groups showed that ossification increased with aging; however, some cases of completely open sutures were observed in the >20-year age groups. The results of the present study are consistent with those of previous studies ( 10 , 11 , 18 , 25 ). Nguyen (2008) carried out a study on 20 patients over 70 years of age and reported that the midpalatal suture is the only suture that might not close completely even in the elderly ( 11 ).…”
Section: Discussionsupporting
confidence: 94%
“…Rapid maxillary expansion (RME) is a procedure with a long history and is the most effective orthopedic approach for expanding and increasing the transverse dimension and correcting the transverse discrepancies through increasing the intermolar width, opening the midpalatal suture and separating the two halves of the maxillary bone with the use of forces of large magnitude ( 1 – 9 ). Gradually, the two halves of the maxillary bone interdigiated to some extent and cannot be separated from each other even with force and in-office appliances; the only way to separate the two halves is through surgery or surgically assisted rapid maxillary expansion (SARME) ( 10 ). Contrary to other cranial sutures, the midpalatal suture in human beings is the only suture that might not close up in the elderly ( 11 ); thus, decision to carry out SARME or RME should not be made only based on the chronological age ( 10 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies support the theory that the midpalatal suture may be the only cranial suture that does not achieve full ossification because of the constant mechanical stress that is applied to it. 35 , 36 Histological studies have demonstrated that caution should be taken when defining the stage of ossification using imaging exams. 35 , 37 …”
Section: Discussionmentioning
confidence: 99%